2017
DOI: 10.1161/atvbaha.117.309430
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adipose Tissue Endothelial ADAM17 in Age-Related Coronary Microvascular Dysfunction

Abstract: Objective A disintegrin and metalloproteinase ADAM17 (TNF-α converting enzyme) regulates soluble TNF levels. We tested the hypothesis that aging-induced activation in adipose tissue (AT)-expressed ADAM17 contributes to the development of remote coronary microvascular dysfunction (CMD) in obesity. Approach and Results Coronary arterioles (CA,~90 μm) from right atrial appendages and mediastinal AT were examined in patients (age:69±11yrs.,BMI:30.2±5.6) who underwent open-heart surgery. CA and AT were also studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 64 publications
4
31
0
Order By: Relevance
“…For example, previous studies have implicated ADAM17 in the regulation of several substrates involved in the pathogenesis of DR including TNFα, TNFRI/II, IL-6R, p75NTR, and ICAM-1 [9,10,[12][13][14][15][16]. Our data are consistent with previous reports showing that ADAM17 contributes to multiple vascular pathologies [28][29][30]. In particular, studies in brain microvascular endothelial cells demonstrated an important contribution of ADAM17 to vascular barrier impairment in response to hypoxia [32].…”
Section: Discussionsupporting
confidence: 92%
“…For example, previous studies have implicated ADAM17 in the regulation of several substrates involved in the pathogenesis of DR including TNFα, TNFRI/II, IL-6R, p75NTR, and ICAM-1 [9,10,[12][13][14][15][16]. Our data are consistent with previous reports showing that ADAM17 contributes to multiple vascular pathologies [28][29][30]. In particular, studies in brain microvascular endothelial cells demonstrated an important contribution of ADAM17 to vascular barrier impairment in response to hypoxia [32].…”
Section: Discussionsupporting
confidence: 92%
“…Aging is often accompanied by an irreversible decline in physiological function, especially metabolic function. The age‐associated metabolic phenotype, including decreased energy expenditure, increased fat mass accumulation, and insulin sensitivity deterioration (Guillory et al, ), can ultimately lead to age‐associated metabolic dysfunction, which correlates closely with several disease, such as type 2 diabetes (Lin et al, ), fatty liver (Gong, Tas, Yakar, & Muzumdar, ; Sheedfar et al, ), cardiovascular diseases (Dou et al, ), neurodegenerative diseases (Martocchia et al, ), and cancer (Topuz et al, ). Thus, exploring the underlying mechanisms of the age‐associated metabolic phenotype and developing drugs to treat aging‐associated metabolic dysfunction are of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…In vascular smooth muscle cells, oxidized low-density lipoprotein in vitro or hyperlipidemia in vivo impaired phagocytosis of apoptotic cells leading to the development of secondary necrotic cells capable of releasing both IL-1α and IL-1β further propagating the inflammatory response. Mice maintained on a high-fat diet also displayed increased activation of ADAM17 on the vascular endothelium, indicating that proteolytic degradation of apoptotic receptors may contribute to impaired phagocytosis during obesity and hyperlipidemia ( 230 ). Targeting hyperlipidemia using atorvastatin, restored phagocytic function to retinal pigment epithelial cells treated with cholesterol crystals or oxidized low-density lipoproteins ( 231 ), demonstrating a proof-of-principle approach to mitigating detrimental effects of hyperlipidemia on phagocytosis in the heart.…”
Section: Molecular Modulators and Inhibitors Of Cardiac Phagocytosismentioning
confidence: 99%